Seroepidemiology of Peste des Petits Ruminants in central Tanzania alongside an evaluation of filter paper as transport medium - Roos, Nils (2016)
Peste des Petits Ruminants (PPR) is a disease of increased attention since the eradication of Rinderpest virus (RPV) in 2011. PPR is an acute and highly contagious viral disease of small ruminants caused by a Morbillivirus named Peste des petits ruminants virus (PPRV). The devastating effects of PPR are mostly present in developing countries, where herding of small ruminants like goat and sheep is a major source of income for millions of farmers. Therefore, PPR is indubitably a disease of major socioeconomic impact. The FAO recently announced a program to eradicate PPR by 2030. The purpose of this study is to evaluate the diagnostic use of filter paper as sample medium in serology analysis for evidence of PPR in sheep and goat in field conditions. The evaluation is performed alongside an epidemiologic screening of PPR antibodies in domestic small ruminants with and without wildlife contact in the Morogoro region, central Tanzania. Present study show that filter paper like Nobuto’s and Sartorius 3MM filter paper soaked with whole blood can be a viable alternative to serum samples, and successive serology through cELISA, in areas where keeping a sustained cold chain is problematic. This study also presents arguments showing how the interpretation of filter paper results could refine and supplement the identification of animals having antibodies against PPRV. Raising the cutoff value in the interpretation of positive individuals from serologic analysis of filter paper samples can improve the accuracy of this method. The serologic screening show that PPRV infection is present in three out of three areas adjacent to the wildlife preservation area Selous Game Reserve. It is of great interest to further evaluate the use of filter paper as an alternative to serum samples in PPR serology to assist the study of PPR in remote areas.